MODELS AND METHODS OF RISK MANAGEMENT IN MORTGAGE LENDING - Anna V. Vorobeva (Plekhanov Russian University of Economics, 2017)
The article considers different risks of mortgage lending. It describes the basic causes of risks, methods for their identification and evaluation; as well the article lists and analyzes the main methods of reducing the potential damage. All described methods and models are systematized and presented in tabular form. The article evaluates the impact of risk on the interest income of the bank and proves the need of effective credit policies. It is also shown how the effective risk management can reduce the cost of credit as for the lender so to the borrower. The work offers some new advanced approaches for risk management of mortgage lending in the Russian banking sector and describes the ways how mortgage products can be improved.